“The great worth of the people”: Models of Community in Joseph Conrad’s Nostromo - Martín Salván, Paula (Estudios Ingleses de la Universidad Complutense, 2009)
In his “Author’s Note” to Nostromo, Joseph Conrad defines Nostromo, the character, as “a man of the People”. A particular notion of community is implicit in the denomination “the People” which I would like to explore in this article. For that purpose, I will draw on classical analyses of the novel in social and political key, as well as on recent theorizations of the concept of community. I would like to examine the way in which Conrad’s idea of “the People” is articulated in the discourse of the narrator and the main characters in the novel. Nostromo may be read as the story of the creation of one specific kind of community: the Occidental Republic of Sulaco, in which concepts such as Nation or Citizenship —which in turn can constitute models of community— are embedded in and contributing to its birth. I will claim, however, that the kind of community advocated by Conrad in his “Note” does not coincide with any of these institutionalized models, but proposes instead an alternative one, characterized by its evasiveness and instability.
Keywords: Community; Nationalism; Solidarity; Myth; Political discourse